2014
DOI: 10.1371/journal.pone.0104623
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Affects Toxin Production by Gymnodinium catenatum

Abstract: The paralytic shellfish toxin (PST)-producing dinoflagellate Gymnodinium catenatum grows in association with a complex marine bacterial community that is both essential for growth and can alter culture growth dynamics. Using a bacterial community replacement approach, we examined the intracellular PST content, production rate, and profile of G. catenatum cultures grown with bacterial communities of differing complexity and composition. Clonal offspring were established from surface-sterilized resting cysts (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…Regarding the microbiome influence on PST content and profile, building evidence favors the hypothesis of an indirect influence of the microbiome, through mediation of dinoflagellate cell physiological processes, rather than direct bacterial PST production (Green et al, 2010;Bolch et al, 2011;Albinsson et al, 2014). Albinsson et al (2014), using cyst germination and controlled microbiome manipulation, have elegantly shown that changes in the cultureassociated microbiome influence the PST profile and net PST production in G. catenatum. In addition, these authors observed an almost 8-fold reduction in the mean net toxin production rate in offspring cultures, relative to parent cultures, suggesting the sexual process involved in cyst formation also plays an important role in toxin modulation.…”
Section: Toxin Profile Of Gymnodinium Catenatummentioning
confidence: 98%
See 3 more Smart Citations
“…Regarding the microbiome influence on PST content and profile, building evidence favors the hypothesis of an indirect influence of the microbiome, through mediation of dinoflagellate cell physiological processes, rather than direct bacterial PST production (Green et al, 2010;Bolch et al, 2011;Albinsson et al, 2014). Albinsson et al (2014), using cyst germination and controlled microbiome manipulation, have elegantly shown that changes in the cultureassociated microbiome influence the PST profile and net PST production in G. catenatum. In addition, these authors observed an almost 8-fold reduction in the mean net toxin production rate in offspring cultures, relative to parent cultures, suggesting the sexual process involved in cyst formation also plays an important role in toxin modulation.…”
Section: Toxin Profile Of Gymnodinium Catenatummentioning
confidence: 98%
“…The biotic and/or abiotic factors determining the differences between PSTs from cyst and plankton-derived cultures are still poorly understood and assumed to be related to the physiological process of encystment/excystment and its interplay with culture conditions (Negri et al, 2007;Hallegraeff et al, 2012;Albinsson et al, 2014). Several works have recently been published on the influence of the accompanying bacterial community (microbiome) on the physiology of Gymnodinium catenatum in culture (Green et al, 2010;Bolch et al, 2011;Albinsson et al, 2014).…”
Section: Toxin Profile Of Gymnodinium Catenatummentioning
confidence: 99%
See 2 more Smart Citations
“…Culture-related factors (growth temperature, medium, and chain-length) are known to significantly alter both total STX content as well as the presence and relative (mol%) proportions of STX derivatives (Band-Schmidt et al, 2006). The composition of the associated culture bacterial community can also influence toxin content and profile, either directly by inter-conversion of toxins produced by the dinoflagellate (see Smith et al (2002) re Alexandrium minutum) or indirectly via their influence on G. catenatum growth rate and cell physiology (Albinsson et al, 2010). Comparisons of profiles obtained from the same strain by different laboratories suggest consistent differences in PST chromatogram interpretation, partly due to limited availability of verified standards for particular STX derivatives.…”
Section: Saxitoxin Profilesmentioning
confidence: 99%